The Antecedents of Customer Loyalty: Attitudinal and Behavioral Perspectives Based on Oliver’s Loyalty Model - Kumar, Amresh; Gupta, S. L.; Kishor, Nawal (Indian Journal of Marketing, 2016)
Purpose: Customer loyalty is picking up significant enthusiasm from scholastics and business experts on the grounds that both are intrigued by knowing the main thrusts that enhance an organization’s competitiveness. Regardless of the imperativeness of customer loyalty, there is still an absence of exhaustive work to investigate how a customer develops loyalty to a specific retailing outlet. The primary objective of this paper was to investigate the antecedents of customer loyalty from both attitudinal and behavioral points of view based on Oliver’s Loyalty model. Design/Methodology/Approach: The study setting is on retail-shopping in India, which concentrates on the departmental stores. The information was gathered from selected departmental stores within the National Capital Region (NCR), India. The instrument utilized as a part of the study was a self- administered survey. With respect to the factual examination, structural equation modeling was used to test the theory/hypothesis. Findings: The study unveiled that the antecedents of cognitive loyalty are the components of store image. They are : store atmosphere, facilities, merchandise, service quality, and transparency in transaction. There are three strategic tools that rule the attitudinal perspective, in particular, store picture, customer satisfaction, and loyalty program. The study concluded that the Indian departmental stores’ customer loyalty level is evolving in stages. Hence, the establishment of attitude-behavior relationship has a great meaning to the retailers due to its predictive power, particularly in marketing strategy formulation. Originality/Value: In the Indian context, this is the first time customer loyalty has been studied from the perspective of Oliver’s four stage loyalty model.